Small and medium enterprise promotion through local capacity building - Maskay, Bishwa Kesher; Centre for Development and Governance (Kathmandu, Nepal). (Kathmandu, Nepal Center for Development and Governance, 1999)
With reference to Nepal.
Keywords: Small business -- Nepal; Business enterprises -- Nepal; Industrial promotion -- Nepal; Entrepreneurship -- Nepal